Bridging Coronary Physiology Into Clinical Application of Acute Coronary Syndrome - Hardi Darmawan (Conferences of Medical Sciences Dies Natalis, 2019)
Normal arteries have three layers of structure, tunica intima, tunica media, and tunica adventitia. Intima tunica is the deepest layer of coronary arteries in which there are antithrombotic molecules such as heparin sulfate, thrombomodulin, and plasminogen activator. In addition, tunica intima also contains substances that regulate the contraction of tunica smooth muscle cell media, called nitric oxide (vasodilators) and prostacyclin (vasoconstrictors). Tunica intima and tunica media seem to be directly related to the atherosclerosis process. Meanwhile, the role of tunika adventisia is unknown. The accumulation of atherosclerotic lesions and hemodynamic stress factors and the degradation of extracellular matrix will cause susceptibility of atherosclerotic plaque fibrous capsules to rupture and form thrombus. Thrombus that occurs in the coronary condition causes acute coronary syndrome, characterized by typical symptoms such as chest pain depending on the thrombus formed. In studying acute coronary syndromes, of course it cannot be separated from understanding the physiology of coronary arteries and the process of atherosclerosis. Therefore, this article aims to briefly explain coronary physiology.